Use Ordinary Expressions to Learn How to Extract Code Feedback From the Software Program Upkeep Process - Anggara Trisna Nugraha Angga; Muhammad Jafar Shiddiq; Moch Fadhil Ramadhan (International Journal of Advances in Data and Information Systems, 2021)
Software engineering is the manner of making use of engineering studies and alertness packages to the design, improvement and renovation of software program. For software program builders or college students majoring in data engineering, the software program renovation manner is a totally complicated activity. Software renovation manner charges account for 40% to 80% of the whole software program engineering manner. The software program renovation manner is resulting from based programming, inadequate understanding domains, and application documentation. In this study, researchers attempted to apply the Java programming language and c / c ++ to deal with supply code truncation. After finishing this manner, this system code may be divided into code and remarks. This report could be used to gain data approximately the manner of knowledge this system from the software program renovation manner. For supply code slicing, the writer makes use of normal expressions, specifically textual content processing strategies or patterns. Using normal expressions can accelerate the manner of locating remarks to your application. The end result of this study is to construct software primarily based totally on open supply code (loose license) so that scholars and trendy programmers can use it to assist apprehend this system. According to the effects of the researchers' testing, the recuperation price is 100% and the accuracy is 100%.